Currents of Change: the Future of Polar Information. Proceedings 22nd Polar Libraries Colloquy, June 2-6, 2008, Edmonton, Alberta, Canada ... : PLC Proceedings ... - Campbell, Sandy; Maloney, Elaine (University of Alberta Library, 2008)
Papers presented at the 22nd Polar Libraries Colloquy held June 2-6, 2008 at the University of Alberta, Edmonton, Alberta, Canada. This conference was held jointly with the University of the Arctic Council Meeting. ...